A hierarchical approach in the diagnostic workflow of chronic myelomonocytic leukemia: Pivotal role of the "Mono‐dysplasia‐score" combined with flow cytometric quantification of monocyte subsets. (24th October 2019) - Zhu, Jaja; Sourdeau, Elise; Aubert, Honorine; Clauser, Sylvain; Maillon, Agathe; Capron, Claude; Jondeau, Katayoun; Ronez, Emily; Schillinger, Francoise; Garnache‐Ottou, Francine; Cornet, Edouard; Bardet, Valérie
Abstract: Introduction: Monocytosis is a frequent trigger for blood smear review in a routine hematology laboratory whereas chronic myelomonocytic leukemia (CMML) is infrequent and arises mostly in elderly patients. In order to define the best workflow for monocytosis, we studied three diagnostic approaches: the classical morphology approach (blood smear review), the flow cytometry assay (quantification of monocyte subsets as described by Selimoglu‐Buet et al in 2015), and the "mono‐dysplasia‐score" also referred to as "Monoscore (as described by our team in 2018 using the structural parameters of the Sysmex XN™ analyzers). Methods: Studying a multicentric cohort of 196 nonclonal monocytoses and CMML patients aged over 50 years, we compared the diagnostic performance of the three approaches alone and in combination to propose a diagnostic decision tree. Results: In patients presenting with additional criteria for slide review to monocytosis (37% of our cohort), we propose to sequentially combine morphology, Monoscore, and flow cytometry. On the contrary, for patients with isolated monocytosis (63%), slide review is not mandatory and we suggest performing flow cytometry depending on the Monoscore value. Using the proposed algorithm, 98% of CMML patients would have been correctly identified, slide review rate drastically reduced, and flow cytometry would have been carried out in 44% of patients. Conclusion: We have shown that implementation of Monoscore is a useful input filter to significantly reduce slide reviews without losing sensitivity and that flow cytometry is a performant technique in the second step of the diagnostic workup of CMML.